Subtle tarsometatarsal ligament injury in a professional ballerina: weight-bearing computed tomography technical tip - Alexandre Leme Godoy-Santos; Carlos Felipe Teixeira Lobo; Dov Lagus Rosemberg; Rafael Barban Sposeto; François Lintz; Cesar de Cesar Netto (Journal of the Foot & Ankle)
Early detection of Lisfranc instability is critical for improving clinical outcomes, but diagnosing subtle injury can be challenging. Magnetic Resonance imaging associated with weight-bearing computed tomography (WBCT) allows evaluation of such injuries in 3 dimensions (3D) under physiologic load. This WBCT technical tip aimed to assess the utility of the 3D measurements between medial cuneiform and the base of the second metatarsal (C1-M2), between the medial and intermediate cuneiforms (C1-C2), and between the first and second metatarsals (M1-M2) to diagnose subtle injury in isolated ligamentous Lisfranc injuries. Level of evidence V, Therapeutic studies, Expert opinion.